Efektivitas Penerapan Model Problem-Based Learning pada Mata Pelajaran Instalasi Motor Listrik - M FARID ALFRED; Aswardi Aswardi (Jurnal Pendidikan Teknik Elektro, 2023)
This study aims to determine the effectiveness of applying Problem Based Learning as a learning model in the class XI TITL electric motor installation subject at SMKN 5 Padang. Practical learning, especially in learning to install electric motors, problems are often found in circuits when carrying out practices such as motors that cannot start. Problem Based Learning is very suitable for use in this lesson so that students are accustomed to solving possible problems that occur when carrying out practical use of electric motors. This study used a quantitative approach with a quasi-experimental method with a pretest posttest nonequivalent control group design. The object of this research is Problem Based Learning and the effectiveness of its application to learning outcomes in the Electric Motor Installation subject. The subjects in this study were students of class XI TITL SMKN 5 Padang. The research instrument used was in the form of pretest and posttest questions in the form of objectives and practice assessment sheets. Based on the average value of the posttest, and practice worksheets are in the high category. Therefore the application of Problem Based Learning as a learning model in electric motor installation subjects is said to be effective because the classical value and effect size are in the high category.